2015
DOI: 10.4085/1062-6050-50.11.01
|View full text |Cite
|
Sign up to set email alerts
|

Landing Technique and Performance in Youth Athletes After a Single Injury-Prevention Program Session

Abstract: Context: Injury-prevention programs (IPPs) performed as season-long warm-ups improve injury rates, performance outcomes, and jump-landing technique. However, concerns regarding program adoption exist. Identifying the acute benefits of using an IPP compared with other warm-ups may encourage IPP adoption.Objective Intervention(s): Participants were stratified by age, sex, and sport and then were randomized into 1 protocol: IPP, SWU, or DWU. The IPP consisted of dynamic flexibility, strengthening, plyometric, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 49 publications
1
45
1
1
Order By: Relevance
“…One study 15 demonstrated changes in LESS scores for both groups, while three studies 14,16,17 demonstrated changes for the IPP groups only.…”
Section: Results Of Searchmentioning
confidence: 99%
See 4 more Smart Citations
“…One study 15 demonstrated changes in LESS scores for both groups, while three studies 14,16,17 demonstrated changes for the IPP groups only.…”
Section: Results Of Searchmentioning
confidence: 99%
“…• Root et al 16 identified significant changes in LESS scores immediately following one IPP session. The authors also examined changes in other outcome measures such as the vertical jump, long jump, or shuttle run.…”
Section: Results Of Searchmentioning
confidence: 99%
See 3 more Smart Citations